Public sector accountability - evidence from the auditor general's reports / Juliana Shariman, Anuar Nawawi and Ahmad Saiful Azlin Puteh Salin. - Shariman, Juliana; Nawawi, Anuar; Puteh Salin, Ahmad Saiful Azlin (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
This study aimed to identify the common issues frequently raised in the Auditor General’s reports and to investigate whether the levels of inefficiencies quoted in the Auditor General’s reports keep increasing or decreasing during the period of investigation. This study was based on the secondary data of Auditor’s General report and was supported with feedback reports received from the ministry, department, state, and agency of the government. This study found that not in compliance with procedures recorded the highest issues highlighted in the Auditor General’s report, followed by the procurement and asset management. In addition, all the issues showed a decreasing trend for both federal government and statutory bodies, indicated an improvement in the efficiencies of management and higher accountability have been demonstrated by the civil servants.